GROUP ART THERAPY USING PHENOLOGICAL PSYCHOLOGICALTOOLS FOR CHILDREN DIAGNOSED WITH HIGH FUNCTIONING AUTISMSPECTRUM DISORDER: DESCRIPTION OF PHENOLOGICAL DISCUSSIONIMPLEMENTATION AND OUTCOMES. - Krasno, Maayan (E-Journal VFU, 2024)
The current research examined the effects of a group art therapy intervention, using phenomenological psychological methods, on the emotional and social skills of children with HFA and to what degree can they reflect on their own and others’ artwork. Thirteen children (6-12 year old) with high functioning Autism, in three small age groups, who attend special education classes in regular schools in Israel, participated in an eight-month weekly intervention. The current article focuses on the phenomenological discussion at the end of each session, where the children learned to observe and reflect on their own and others’ artworks using the phenomenological language. All the children, even the younger ones, eventually adopted this language and some even continued to implement it after its conclusion. All of them exhibited improved emotional understanding and expression, and social skills. Focusing on the concrete artworks, in a safe environment with clear and consistent settings and rules helped them achieve these changes.